The synthesis, characterisation and photocatalytic activity of TiO2/cellulose nanocomposites - Ballim, Muhammed As’ad (My University, 2020)
In this dissertation, the extraction and characterisation of cellulose fibres from a low-cost maize tassel agricultural waste material was carried out. This was achieved by base treatment of maize tassel using an alkaline treatment approach to produce cellulose I or II, depending on the treatment time, concentration and pre-treatment conditions. The polymer was characterised using XRD, TEM, SEM, Raman spectroscopy, FTIR and EDX. The results obtained showed that cellulose II was the main product and that cellulose fibres could be extracted from the waste maize tassel. Titania was synthesised by a sol-gel method using an alcohol solvent. The nanomaterial produced was then characterised using XRD, Raman spectroscopy, EDX, FTIR, TEM and SEM. It was found that the phase of the titania was anatase and the morphology was spherical. The product formed highly agglomerated structures that also took the form of spherical shapes. These also confirmed the chemical properties of titania. The size of the particles was confirmed by the Scherrer equation and analysis of SEM and TEM images by image J software and was found to be between 8 and 12 nm. The formation of TiO2/cellulose nanocomposites was achieved by a method similar to urea deposition. The two products were meshed together and analysed by SEM, TEM, EDX, FTIR, XRD and Raman spectroscopy. It was found that the titania nanoparticles were attached to the cellulose polymer surface and the cellulose surface coverage increased with an increase in the amount of TiO2used.The composite was then used to treat water contaminated with the organic dye methyl orange. The results obtained from this study indicated that the TiO2/cellulose composite could degrade the MO dye with a lesser concentration of titania attached to the cellulose when compared to bare TiO2.Increasing the concentration of titania on cellulose proved better at degrading the methyl orange dye
A dissertation submitted for the degree of Master of Science, School of Chemistry, Faculty of Science, at the University of the Witwatersrand, 2020